Analysis of Indonesian and English Code-Mixing in Master Chef Indonesia Season 3 - Rakhmasari, Dwi Lia (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
Language is inseparable from human activity. Under certain conditions, people may also change speech or vocabulary. This happens because the speaker is in a demanding state of doing so called code-mixing. In Indonesia, code mixing often happen in some occasions. One of them is in Master Chef Indonesia season 3. This paper aims to analyze the code-mixing that occurs in master chef Indonesia season 3. This is qualitative research. The data were taken from YouTube channel master chef Indonesia then categorized between necessary and unnecessary. It is found 77 sentences that used code-mixing in this show, 30 necessary and 47 unnecessary. The writer concluded that There are two factors why people do code-mixing. The first is because of limited vocabulary, the second is to show their English language skills. Key words: Code-Mixing, Master Chef, Sociolinguistics